SURVEY OF THE SOIL PHYSICAL CHARACTERISTICS OF ABUBAKAR TAFAWA BALEWA UNIVERSITY FARM AS IT’S RELATE TO MOISTURE AVAILABILITY FOR AGRICULTURAL PRODUCTIVITY - Muhammad, Y. I.; Babaji G. A.; Hassan A. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
A detailed survey of the university farm was conducted, using rigid-grid sampling method to obtain one hundred and forty-four (144) soil samples from 4.7 hectares of land. Surface soil samples of 0-15 and 15-30 cm were collected at grid intersection points. The collected soil samples were air-dried and passed through a 2mm sieve, and analyzed using standard laboratory procedures for physical parameters. Undisturbed soil samples were collected in situ using stainless steel core rings for determination of soil moisture release using pressure membrane apparatus, while double ring infiltrometer was used to determine infiltration rates. Simple linear correlation and regression analysis were conducted to establish relationship between the various data obtained. The findings of the research reveal that out of the analyzed samples, 34 samples were identified as clay, 28, 1, 3 and 6 as sandy loam, sand, silty clay and gravelly sand respectively. At 0.33, 0.5 and 1 bar sandy loam was negatively correlated with clay, while at 5, 10 and 15 bars clay was negatively correlated with sandy loam respectively. The simple linear correlation between bulk density and total porosity indicated a negative correlation at both levels. In conclusion, the linear curve fitting for both Horton and modified Kostrakov’s infiltration equations yielded a positive coefficient of determination(R) of 0.992 and 0.982 respectively. Therefore, it is recommended that sandy loam with preponderance of small, medium and large soil particles is capable of retaining soil moisture at different tension levels and should be preferably used for farming activities in the University farm.